Implementing climate-sensitive health counselling: a qualitative study with physicians in Germany - Herrmann, Alina; Griesel, Silvan; Quitmann, Claudia (BMC health services research, 2025)
To protect human health, it is important to improve climate-resilience and mitigate climate change and environmental degradation. Health systems can contribute to this by providing climate-resilient and sustainable health services. One example of such a health service is climate-sensitive health counselling (CSHC), which is defined as communication with patients about climate change and health issues within clinical settings. In this study, we explore how physicians in Germany conduct CSHC and what supports them in doing so with the purpose to better conceptualize CSHC and give recommendations on how to support its implementation.